2006
DOI: 10.1007/s11864-006-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Current therapeutic approaches in patients with brain metastases

Abstract: The development of brain metastases is often viewed as the end stage of a disease course and engenders skepticism about the efficacy of treatment. Aggressive management of brain metastases is effective in both symptom palliation and the prolongation of life. The majority of patients with controlled intracranial metastases will expire from systemic disease rather than from recurrence of these metastases. Single brain metastases should be treated with surgical resection or stereotactic radiosurgery, though it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 55 publications
0
47
0
4
Order By: Relevance
“…Recent studies [28] showed that the blood-brain Barrier (blood brain barrier, BBB) has been destroyed in the process of brain metastases, and with whole brain radiotherapy, mannitol and other dehydration drugs can make the BBB open in a variety degrees, which allows chemotherapy drugs across the blood -brain barrier into the central nervous system to kill tumor cells. Nitrosourea, cisplatin, teniposide, paclitaxel, vermeer, temozolomide are chemotherapy drugs that have been commonly used [29].…”
Section: Chemotherapeuticsmentioning
confidence: 99%
“…Recent studies [28] showed that the blood-brain Barrier (blood brain barrier, BBB) has been destroyed in the process of brain metastases, and with whole brain radiotherapy, mannitol and other dehydration drugs can make the BBB open in a variety degrees, which allows chemotherapy drugs across the blood -brain barrier into the central nervous system to kill tumor cells. Nitrosourea, cisplatin, teniposide, paclitaxel, vermeer, temozolomide are chemotherapy drugs that have been commonly used [29].…”
Section: Chemotherapeuticsmentioning
confidence: 99%
“…This effect is most likely due to elimination of micrometastases that were present at the time [61,62]. External WBRT is thus advantageous and typically considered the mainstay of treatment for most patients with multiple metastatic deposits from melanoma in the brain [38,63,64]. More localized treatment modalities would be less beneficial in such situations because it would require targeting of each lesion individually.…”
Section: Whole Brain Radiation Therapymentioning
confidence: 99%
“…More localized treatment modalities would be less beneficial in such situations because it would require targeting of each lesion individually. However, solitary metastases that are too large for either surgical resection or stereotactic surgery or those that impinge on sensitive areas of the brain are often treated with WBRT [63,65]. The broad application of radiation to the brain can also be an important disadvantage.…”
Section: Whole Brain Radiation Therapymentioning
confidence: 99%
See 2 more Smart Citations